1980
DOI: 10.5636/jgg.32.617
|View full text |Cite
|
Sign up to set email alerts
|

North-south anisotropy and radial density gradient of galactic cosmic rays.

Abstract: The cosmic ray north-south anisotropy arising from the heliocentric radial density gradient of cosmic rays and the interplanetary magnetic field has been studied using data for a wide range of rigidity (15-210 GV in median primary rigidity) during the period 1969-1973. Two components of the anisotropy; the north-south asymmetry and the associated sidereal diurnal variation have been analyzed to reveal a three-dimensional structure of the anisotropy in space. By means of the least-squares method and using impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
40
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 11 publications
16
40
0
Order By: Relevance
“…They found no dependence of Gr on the polarity of the IMF in agreement with spacecraft observations and verified at higher rigidities (Yasue 1980, Swinson 1988), although Yasue found no significant variation in Gr from 1968 to 1972.…”
Section: Radial Density Gradientsupporting
confidence: 72%
See 2 more Smart Citations
“…They found no dependence of Gr on the polarity of the IMF in agreement with spacecraft observations and verified at higher rigidities (Yasue 1980, Swinson 1988), although Yasue found no significant variation in Gr from 1968 to 1972.…”
Section: Radial Density Gradientsupporting
confidence: 72%
“…This method of inferring the IMF sector was shown to be in about 75% agreement with spacecraft measurements of the sector type. Yasue (1980) derived the spectrum of r,Ts for the combined years 1968 to 1972. He found that the anisotropy was wealdy proportional to the rigidity of the particles (P 0-3) and that Pu was between 150 and 300 GV.…”
Section: Characteristics Of the Sidereal (North-south) Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…Yasue (1980) analyzed the GG-component together with the sidereal diurnal variation observed by MDs and NMs and derived the power law-type rigidity spectrum of the average NS anisotropy with a positive power law index of approximately 0.3. By analyzing long-term variations of the 3D anisotropies observed with Nagoya MD and NMs on yearly basis, Munakata et al (2014) confirmed that the perpendicular component including the NS anisotropy increases with GCR rigidity.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The ecliptic component has been derived from the amplitude and phase of the solar diurnal anisotropy in many papers [4,5,6], while the north-south anisotropy (NSA) parallel to the Earth's rotation axis has been derived from NM and MD data in a couple of different ways [7,8,9]. Mori and Nagashima (1979) [10] proposed a way to derive the NSA from the "GG-component" of a single multi-directional MD at Nagoya in Japan.…”
Section: Introductionmentioning
confidence: 99%